Effect of Central Nervous System Metastases on Treatment Discontinuation and Survival in Older Women Receiving Trastuzumab for Metastatic Breast Cancer. (9th April 2012) - Danese, Mark D.; Lindquist, Karla; Doan, Justin; Lalla, Deepa; Brammer, Melissa; Griffiths, Robert I.
Abstract : Background . Trastuzumab improves survival in HER2-positive women with metastatic breast cancer (MBC). The consequences of longer survival include a higher likelihood of additional metastases, including those in the central nervous system (CNS). The effect of CNS metastases on both trastuzumab discontinuation and survival in older patients has not been described. Patients and Methods . We used the Surveillance Epidemiology and End Results (SEER) Medicare data to identify a cohort of 562 women age 66 or older with MBC who were diagnosed between January 1, 2000 and December 31, 2005, free of CNS metastases, and initiated trastuzumab after MBC diagnosis. Time to discontinuation and time to death were analyzed using proportional hazards models. Results . Newly diagnosed CNS metastases were associated with both higher risk of trastuzumab discontinuation (relative hazard [ RH ] = 1.78, 95% CI 1.11–2.87) and higher risk of death (RH = 2.49, 95% CI 1.84–3.37). The incidence rate of new CNS metastases was comparable among various sites of metastasis (10.7 to 14.7 per 1, 000 patient-months), except for bone which was higher (24.1 per 1, 000). Conclusion . The diagnosis of CNS metastases was associated with an increase in both the likelihood of discontinuing trastuzumab therapy as well as the risk of death.